Performance Measurement Using Development Ladder Assessment and Health Indicators: Study of Co-operatives - Ridwan Ibrahim; Donni Deiriadi; Heru Fahlevi (Universitas Syiah Kuala, 2019)
AbstractObjective – This study aimed to analyze the performance of co-operative using two different performance management measures, Development Ladder Assessment (DLA 2009 version) and co-operative health indicator (CHI). Design/methodology – The sample of this study is 10 co-operatives operated in Aceh, Indonesia. Data was collected from secondary and primary sources. The secondary data is obtained from financial reports and annual meeting reports of 2014 and 2016, while primary data was collected from questionnaires with management and supervisory board of the co-operatives. The data was analyzed using a comparative and descriptive statistical approach. Results – This study found that both performance methods produced different results. Some co-operatives attain rank “A” in DLA approach, but no co-operatives are categorized as rank “A” within CHI measure. Additionally, DLA is more informative for the supervisory board in measuring co-operative performance than CHI.